The Most Cited Scientific Information Sources in Wikipedia Articles Across Various Languages - Włodzimierz Lewoniewski (Biblioteka)
Ensuring the accuracy of information in Wikipedia articles requires the use of reliable sources that can be assessed by encyclopedia readers. However, the determination of source reliability can be subjective, with variations based on the language and subject matter of the article. Consequently, each language version of Wikipedia may have its own guidelines for judging the trustworthiness of sources. Some Wikipedia citations lead to scientific resources, which are usually deemed more reliable than websites due to their rigorous peer-review procedures and publication by esteemed academic publishers. This implies that the data presented in these scientific sources has been meticulously examined by specialists in the relevant area, providing a higher level of precision and trustworthiness. In this study, 332,424,439 references from 61,218,277 Wikipedia articles across 309 language versions were analyzed to identify citations to scientific publications. Additionally, OpenAlex was used to find unified metadata of important sources of information of multilingual Wikipedia.